Performance Deterioration of Pitot Tubes Caused by In-Flight Ice Accretion: A Numerical Investigation - Hao Zhang; Rui Zhao; Chih-Yung Wen (International Journal of Aerospace Engineering)
In-flight ice accretion on typical pitot-static systems is numerically investigated to reveal their performance deterioration under both rime and glaze icing. Coupled with the open source computational fluid dynamics (CFD) platform, OpenFOAM, the numerical strategy integrates the airflow determination by the Reynolds-averaged Navier-Stokes equations, droplet collection evaluation by Eulerian representation, and ice accumulation by mass and energy conservation. Under varying inflow conditions and wall temperatures, the calculated ice accretion performance indicates that the ambient temperature has the most significant effect on the icing-induced failure time, leading to an almost exponential growth. Meanwhile, the blocking time is found to be linearly proportional to the increase in wall temperature. With the increase in inflow velocity, the failure time follows a parabolic variation with glaze ice accretion while shows a monotonic reduction under rime icing conditions. In addition, when the angle of attack increases, failure accelerates under both the glaze and rime icing scenarios. These findings provide guidance for the protection design of pitot tubes. A nonlinear regression analysis is further conducted to estimate the failure performance. The predicated failure times show reliable consistency with numerical results, demonstrating the capability of the obtained empirical functions for convenient predictions of failure times within the applicable range.